ANALISIS DAN ALTERNATIF SOLUSI LALU LINTAS DI BUNDARAN JALAN TEUKU UMAR DENPASAR - Pandu Abraham Saleh; Umbu Jesse Ratudima; Bambang Pudjianto; YI. Wicaksono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
The volume growth of road traffic continues to increase rapidly especially in the city of Denpasar. This makes the traffic jam occurred in the city of Denpasar on rush hour, especially at Teuku Umar roundabout. The aim of research is to evaluate and find solustion occlusion at Teuku Umar roundabout. In the case try solution of traffic engineering and Development underpass .Data collection is done by a direct survey on six approaches at the foot of the roundabou at the peak hour of the morning, afternoon and evening. The captured data is the number of vehicles passing through the street that enter and roundabout exit. Analysis of the performance of the roundabout by using the guidelines Indonesia Highway Capacity Manual (MKJI) 1997. The results of the performance of the roundabout on the existing condition have average delay in roundabout 16,98 sec/hours at condition scenario 1 with traffic engineering average delay in roundabout drop to 8,07 sec/hours consequence incresing the number of venicles on Teuku Umar Timur street, Teuku Umar Barat street, Imam Bonjol street, Diponegoro street which degree of saturation before 0,43, 021, 0,55, 0,64 and after the traffic egineering rise to 0,58,0,24,0,66, 0,80. In scenario 2 with development underpass average delay in roundabout drop to 4,53 sec/hours and value is smaller than scenario 1 traffic engineering to overcome congestion at Teuku Umar roundabout its recommendation scenario 2 development underpass. Development underpaas could occur when land acquistion well prepared.